Private Education : Studies in Choice and Public Policy. - Levy, Daniel C. (Yale studies on nonprofit organizations., 1986)
This book focuses on the relationship between private and public education in a comparative context. The contributors emphasize the relationship between private choices and public policy as they affect the division of labor between public and private non-profit schools, colleges, and universities. Their essays examine the kinds of choices offered by each sector, as well as the effects of present and proposed public policies on the intersectoral division of labor. Written from neither a pro-private nor a pro-public point of view, the contributors point to the ways in which they believe one sect.